2019
DOI: 10.13004/kjnt.2019.15.e36
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Hemoglobin A1c Levels for the Detection of Post-Surgical Infection Following Single-Level Lumbar Posterior Fusion in Patients with Diabetes

Abstract: ObjectiveSeveral studies have reported that patients with diabetes mellitus (DM) are vulnerable to infection. However, the mechanism underlying this remains unclear. We hypothesized that preoperative blood glucose levels in patients with DM may be a risk factor for surgical site infection (SSI). We aimed to investigate the relationship between hemoglobin A1c (HbA1c) level and SSI incidence following single-level spinal fusion surgery.MethodsPatients with DM who underwent single-level lumbar posterior fusion su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 27 publications
(44 reference statements)
0
26
0
Order By: Relevance
“…Of these, 4 studies reported extensive postoperative follow-up of over 1 year; 3 of these studies utilized HbA1c threshold ranging from 6.5-6.9%, and indicated that elevated values above threshold were associated with poor long-term functional outcomes, increased nonunion rate, decreased fusion rate, and increased infection rate following PLF. 28 - 30 The remaining study with 1 year follow-up reached similar conclusions but utilized a higher HbA1c threshold (7.5%). 31 Considering that HbA1c thresholds <7.5% still resulted in adverse postoperative outcomes, using lower values to gauge postoperative risk may be more recommended.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Of these, 4 studies reported extensive postoperative follow-up of over 1 year; 3 of these studies utilized HbA1c threshold ranging from 6.5-6.9%, and indicated that elevated values above threshold were associated with poor long-term functional outcomes, increased nonunion rate, decreased fusion rate, and increased infection rate following PLF. 28 - 30 The remaining study with 1 year follow-up reached similar conclusions but utilized a higher HbA1c threshold (7.5%). 31 Considering that HbA1c thresholds <7.5% still resulted in adverse postoperative outcomes, using lower values to gauge postoperative risk may be more recommended.…”
Section: Discussionmentioning
confidence: 64%
“…Four studies reported on the association between elevated HbA1c and adverse postoperative outcomes following PLF. [27][28][29][30] Takashi et al reported that elevated HbA1c was associated with increased VAS scores for low back pain at final follow-up (29.3 vs 17.9, p < 0.013, Table 8). Moazzeni et al reported that VAS scores were significantly different between patients with elevated vs. normal HbA1c for the first 2 weeks postoperatively (5.4 vs 4.4, p ¼ 0.003, Table 8) but reported that VAS scores were no longer significant after 6 months (4.2 vs 3.6, p ¼ 0.08, Table 8).…”
Section: Plfmentioning
confidence: 99%
“…Therefore, cases requiring revision due to infection are relatively rare. In the posterior approach, prolonged CRP normalization occurred in 26.1% (24/92) of the cases and revision for abscess drainage was required in 3.2% (3/92) of the cases [ 13 ]. However, prolonged CRP normalization was found to be low at 4.9% (7/143).…”
Section: Discussionmentioning
confidence: 99%
“…If CRP rebounded without other infectious causes (e.g., urinary tract infection, pneumonia, etc. ), additional antibiotics were administered until CRP normalization [ 13 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hwang, J. U. team discovered that hb1c level more than 6.9% would increase the risk of getting SSI [29]. Peng, W. concluded that during 6 years of retrospective study of 523 Diabetes Mellitus patient who went for lumbar surgery, 7.1% got SSI, superficial infection accounted for 4.2% and deep infection made up 2.9% [30].…”
Section: Incidencementioning
confidence: 99%